2014
DOI: 10.1089/ten.tea.2012.0615
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Survival and Function of Islet-Like Clusters Differentiated from Adipose Stem Cells on a Three-Dimensional Natural Polymeric Scaffold: AnIn VitroStudy

Abstract: Autologous adipose stem cells owing to its pluripotent nature offer a valuable source for pancreatic beta cell replacement in the treatment of diabetes mellitus. However, maintaining longevity and functionality of stem cell-derived islet-like cells for long-term in vitro culture is challenging. Signaling interaction between islets and surrounding extracellular matrix (ECM) is an important factor for islet survival and function. Tissue engineering strategy to use scaffolds as substitute for ECM is a key to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
62
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 47 publications
3
62
2
Order By: Relevance
“…Moreover, most of these studies failed to generate a sufficient amount of islets for human transplantation and long-term stability. Recent progress in tissue engineering suggested that a biocompatible scaffold may be necessary for the in vitro generation of artificial islets with functional vasculature from stem cells [73]. In our recent study [74], we confirmed that the administration of MSCs into the pancreatic microenvironment can indeed improve the symptoms of diabetes.…”
Section: Mesenchymal Stem Cells In Treatment Of Diabetes Mellitus Typesupporting
confidence: 72%
“…Moreover, most of these studies failed to generate a sufficient amount of islets for human transplantation and long-term stability. Recent progress in tissue engineering suggested that a biocompatible scaffold may be necessary for the in vitro generation of artificial islets with functional vasculature from stem cells [73]. In our recent study [74], we confirmed that the administration of MSCs into the pancreatic microenvironment can indeed improve the symptoms of diabetes.…”
Section: Mesenchymal Stem Cells In Treatment Of Diabetes Mellitus Typesupporting
confidence: 72%
“…In another example, adipose stem cells seeded in a 3D biodegradable scaffold composed of natural polymers dextran and gelatin can effectively differentiate to islet-like clusters expressing islet-specific hormones (e.g. insulin, glucagon, and somatostatin) (Aloysious & Nair, 2013). With the scaffold method, the 3D organization of b cells can be controlled and their functions can be improved through cell-cell interaction by tuning the scaffold architecture.…”
Section: Other Methodsmentioning
confidence: 99%
“…Differentiation was accomplished following our published protocol (Aloysious & Nair, 2014). Differentiation was accomplished following our published protocol (Aloysious & Nair, 2014).…”
Section: Differentiation Of Isletsmentioning
confidence: 99%
“…This is highly advantageous for efficient nutrient and oxygen exchange for the cells cultured in these 3D scaffolds (Aloysious & Nair, 2014;Vaikkath et al, 2016). This high water absorption capability can be attributed to the hygroscopic nature of PCL-PTHF-PCL triblock copolymer and wicking action of more number of nanofibers in the lattice scaffold.…”
Section: In Vivo Studiesmentioning
confidence: 99%
See 1 more Smart Citation